Growing pigs fed cassava peel based diet supplemented with or without Farmazyme® 3000 proenx: Effect on growth, carcass and blood parameters - A. O. K. Adesehinwa; O. O. Obi; B. A. Makanjuola; O. O. Oluwole; M. A. Adesina (African Journal of Pig Farming, 2018)
36 growing pigs (average initial weight of 22.74 ± 0.88 kg) were allotted to three dietary treatment groups of 30%maize-based control diet and 30%cassava-peel-based diet supplemented with or without Farmazyme 3000 proenx. Each treatment had three replicates of 4 pigs/replicate (12 pigs/treatment) in a complete randomized design. The pigs were allowed AD LIBITUM access to the diets and water throughout the 42-day duration of the trial. The replacement of the 30% maize in the control diet with cassava peel resulted in increased bulkiness and crude fiber contents of the cassava peel-based diets, hence, lowered energy content. There was also a reduction in the dry matter intake of the pigs and the cost of feed per kg intake by 19.6 and 23.5% for the cassava peel based diet with and without Farmazyme inclusion, respectively. The replacement of the maize content of the control diet with cassava peel resulted in 23 to 24% reduction in the cost of feed per kg live weight gain of the growing pigs. Farmazyme resulted in enhanced utilization (P < 0.05) of the cassava peel-based diet in terms of the daily and overall weight gains as well as the serum total protein, albumin, urea and cholesterol. While the heamoglobin and red blood cell (RBC) of the pigs were significantly positively influenced by the inclusion of the enzyme, it had no effect on the packed cell volume (PCV). The blood minerals (Na, Ca, Cl and P), relative organ weights and dressing percentage of the pigs were neither affected by the cassava peel replacement nor the enzyme inclusion but for the kidney, where lower values were obtained both for the control and Farmazyme supplemented cassava peel-based diets. It could therefore be concluded that, inclusion of Farmazyme 3000 proenx enhanced utilization of the cassava peel-based diet thereby, resulting in performance results comparable to pigs fed the maize-based control diet.